Novel Bovine Papillomavirus Type Discovered by Rolling-Circle Amplification Coupled with Next-Generation Sequencing. - Flavio R C da Silva; Samuel P Cibulski; Cíntia Daudt; Matheus N Weber; Lorena L B Guimarães; André F Streck; Fabiana Q Mayer; Paulo M Roehe; Cláudio W Canal (PLoS ONE, 2016)
Currently, fifteen bovine papillomavirus (BPV) types have been identified and classified into four genera: Deltapapillomavirus, Epsilonpapillomavirus, Dyoxipapillomavirus, and Xipapillomavirus. Here, the complete genome sequence of a new BPV type (BPV 04AC14) recovered from a papillomatous lesion is reported. The genome is 7,282 bp in length and exhibits the classic genetic organization and motifs of the members of Papillomaviridae. Maximum likelihood phylogenetic analyses revealed that BPV 04AC14 clusters with members of the Xipapillomavirus genus. The nucleotide sequence of the L1 capsid protein of the novel BPV is closely related to its counterpart, BPV3, with which it shares 79% similarity. These findings suggest that this virus is a new BPV type of the Xipapillomavirus genus.